2011
DOI: 10.3892/or.2011.1397
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of HIF-1A and its implication in the hypoxia pathway in primary advanced uterine cervical carcinoma

Abstract: Abstract. The development of cervical cancer exhibits some unique differences compared to other solid tumors. Normal cervical stratified epithelia have characteristics of hypoxic tissue. Lack of oxygen (hypoxia) induces the HIF-1 (hypoxiainducible factor-1) transcription factor, which is a heterodimer composed of a constitutively expressed β subunit and a hypoxia-inducible α-subunit. HIF-1A targets the transcription of over 70 genes involved in many aspects of cancer biology. In well-oxygenated environments, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 69 publications
5
17
1
Order By: Relevance
“…To evaluate the statistically significant difference in the ratio of cancerous EPAS1 mRNA level to histopathologically unchanged tissue EPAS1 mRNA level between the three DNA methylation ranges (0%-1% methylation, 1%-10% methylation, and 10%-100% methylation), the nonparametric Kruskal-Wallis test was used. HIF1A mRNA levels were increased in cancerous compared with noncancerous tissue (8,11,12,33,34). However, other studies reported a constant HIF1A mRNA level in tumor cells and suggested mainly posttranslational regulation of HIF1A expression (35)(36)(37), which is consistent with our observations.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…To evaluate the statistically significant difference in the ratio of cancerous EPAS1 mRNA level to histopathologically unchanged tissue EPAS1 mRNA level between the three DNA methylation ranges (0%-1% methylation, 1%-10% methylation, and 10%-100% methylation), the nonparametric Kruskal-Wallis test was used. HIF1A mRNA levels were increased in cancerous compared with noncancerous tissue (8,11,12,33,34). However, other studies reported a constant HIF1A mRNA level in tumor cells and suggested mainly posttranslational regulation of HIF1A expression (35)(36)(37), which is consistent with our observations.…”
Section: Discussionsupporting
confidence: 83%
“…Data about DNA methylation of the HIF1A promoter region are ambiguous. The absence of DNA methylation of the HIF1A promoter was observed in advanced uterine cervical carcinoma and datasets available at ENCODE project, whereas DNA hypermethylation was observed in an immature hematopoietic cell line HMC-1 and normal colon tissues isolated from 20 patients with colorectal cancer (14,34,45). In our studies, DNA methylation of the HIF1A promoter was undetected in a group of 120 patients.…”
Section: Discussionmentioning
confidence: 78%
“…We also did not observe changes in the DNA methylation pattern in the CXCR4 promoter region in either control or cancer tissue samples (data not shown). In our previous report we found significantly increased HIF-1A transcript and protein levels in tumor tissue samples compared to their normal, non-cancer counterpart (29). A statistically significant association was found between HIF-1A (31,32).…”
Section: Reverse-transcription and Real-time Quantitative Pcr (Rq-pcr)mentioning
confidence: 99%
“…HIF1 influences the expression of a diverse set of genes associated with tumor progression, e.g. eritropoyetin (Epo), transferrin, endothelin-1, iNOS, Glut-1 transporter, VEGF and inflammatory molecules as well as pro-and antiapoptotic genes [16][17][18]. Cancer cervix hypoxia has been described to be independent of clinical size, grade and FIGO stage [19,20] and is nowadays considered a powerful independent prognostic factor for the outcome of the disease [11,21].…”
Section: Introductionmentioning
confidence: 99%